Pengaruh Kualitas Pelayanan, Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen Pada Umkm Kopi Dua Gunung Pasuruan Pada Konsumen UMKM Kopi Dua Gunung Pasuruan - Dzulkifli, Muhammad; Widarko, Agus; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract In the current era of globalization in Indonesia occurs very quickly and provides many changes and developments in various fields, conditions like this that require all companies or organizations to be more creative and competitive in dealing with changes and developments that occur. Globalization that occurs in Indonesia occurs in all areas of life including the economic field. One of the businesses that is in great demand in the city of Pasuruan is UMKM that produces coffee. The purpose of this study was to determine and analyze the effect of Service Quality, Product Quality and Price on Customer Satisfaction at Umkm Kopi Dua Gunung Pasuruan. This research method uses quantitative methods. The population in this study were all consumers who had bought UMKM Kopi Dua Gunung Pasuruan. The number of samples used was 96 respondents. The data analysis technique uses descriptive and inferential statistical methods with the help of SPSS. The results showed that service quality, product quality and price had a positive and significant effect simultaneously on customer satisfaction. Service quality has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer satisfaction. Price has a positive and significant effect on customer satisfaction. Keywords: Service Quality, Product Quality, Price, Customer Satisfaction